CT‐guided percutaneous hookwire localization increases the efficacy and safety of VATS for pulmonary nodules. Issue 7 (23rd February 2017) - Klinkenberg, Theo J.; Dinjens, Lars; Wolf, Rienhart F. E.; van der Wekken, Anthonie J.; van de Wauwer, Caroline; de Bock, Geertruida H.; Timens, Wim; Mariani, Massimo A.; Groen, Harry J. M.
Abstract : BACKGROUND AND OBJECTIVES: The diagnosis of pulmonary nodules of unknown origin is challenging, and such nodules are not always suitable for transthoracic needle biopsy. With the advent of video assisted thoracic surgery (VATS) and CT‐guided percutaneous hookwire localization (CT‐PHL) we hypothesized that the combination of these two procedures will improve early diagnosis. METHODS: Selection criteria were a nodule not well approachable with fine needle biopsy and the therapeutic consequences of a diagnosis as assessed by the multidisciplinary oncology board. Efficacy and safety of the combination of CT‐PHL prior to VATS was studied in terms of, histological diagnosis, complete resection rate, complications, conversion rate to thoracotomy, and duration of procedures. RESULTS: A total of 150 pulmonary nodules were located and resected in 150 patients. The median nodule diameter was 9 mm (range 4‐24) and located within 30 mm of the pleural surface (median 7, range 0‐29). The resection was complete in 96%, and in 100% a definitive histological diagnosis was obtained. Complications requiring intervention during the CT‐procedure occurred in 11 patients (7.3%). Complications of VATS consisted of major complications (2.0%) and minor complications (4.0%). The 30 Day mortality was 1.4% and in hospital mortality 0.7%. Conversion to thoracotomy occurred in 4.7% patients. Median CT‐localization time was 25 min (range 5‐72), median VATS time was 49 min (range 14‐169). CONCLUSIONS: CT‐PHL is a very efficient and safe procedure prior to VATS for pulmonary nodules and allows in 96% radical resection with a diagnostic accuracy of 100%.